Anthelmintic effect of Halothamus somalensis in Arsi-Bale goats - Dawo, F.; Tibbo, Markos (2005)
The root of the medicinal plant Halothamnus somalensis traditionally used to treat endo-parasites of animals and humans was evaluated against endo-parasites in naturally infected goats. The goats were drenched with a crude preparation of the plant at two different doses (0.5 and 2 g/kg live weight [LW]). The dose of 2g/kg LW reduced faecal egg count (EPG) by 50%. Packed cell volume (PCV) was also significantly higher for goats that received 2 g/kg LW. The reduction in faecal EPG and increase in PCV values were negatively correlated. There was no effect on LW change but body condition score was higher for goats that received treatment than goats in the control group. Future research should focus on evaluation of different extracts from different parts of the plant using laboratory animals and small ruminants.